Transnationale Konsumgüterunternehmen in Ägypten: Eroberung des Massenmarktes zwischen „ruralem Marketing“ und „Konsumentenintifada“ - Kehrer, Michaela (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
The marketing strategies of transnational corporations operating in the field of consumer goods in contemporary Egypt are analyzed and the interrelations between rural marketing and consumer intifada are explored. The question is raised whether the homogenization scenario of local consumer cultures in the sense of a coca-colaization process is coming into shape. On the contrary to the mainstream assumption, it is stated that since the last decade corporate communication and product policies in their effort to conquer the Egyptian mass market have been increasingly taking cultural spheres of meaning into account. Different indicators show that the relevance of producing and marketing standardized goods has been diminishing as compared to the centrality of adapting global products to the local setting with its various cultural and political components.